Differential regulation of apoptosis-related genes during long-term culture and differentiation of canine adipose-derived stem cells - a functional bioinformatical analysis - Jankowski, Maurycy; Stefańska, Katarzyna; Suchodolski, Michał; Dompe, Claudia; Wąsiatycz, Grzegorz; Kempisty, Bartosz; Nowicki, Michał; Roszak, Magdalena (Frontiers in Genetics, 2025)
IntroductionStem cells derived from adipose tissue are gaining popularity in the field of regenerative medicine due to their adaptability and clinical potential. Their rapid growth, ability to differentiate, and easy extraction with minimal complications make adipose-derived stem cells (ADSCs) a promising option for many treatments, particularly those targeting bone-related diseases. This study analyzed gene expression in canine ADSCs subjected to long-term culture and osteogenic differentiation.MethodsADSCs were isolated from discarded surgical waste and cultured for 14 days with and without differentiation media to assess osteogenic changes. RNA sequencing (RNA-seq) and bioinformatical analysis were performed to obtain comprehensive transcriptomic data. A total of 17793 genes were detected and GO enrichment analysis was performed on the differentially expressed genes to identify significantly up- and downregulated Biological Process (BP) GO terms across each comparison.ResultsThe upregulation of apoptosis-regulating genes and genes related to circulatory system development suggest an induction of these processes, while the downregulation of neurogenesis and gliogenesis genes points to reciprocal regulation during osteogenic differentiation of canine ADSCs.DiscussionThese findings underscore the potential of ADSCs in bone regeneration and offer valuable insights for advancing tissue engineering, however further studies, including proteomic analyses, are needed to confirm these patterns and their biological significance.